Anatomy, feeding ecology, and ontogeny of a transitional baleen whale: a new genus and species of Eomysticetidae (Mammalia: Cetacea) from the Oligocene of New Zealand - Robert W. Boessenecker; R. Ewan Fordyce (PeerJ, 2015)
The Eocene history of cetacean evolution is now represented by the expansive fossil record of archaeocetes elucidating major morphofunctional shifts relating to the land to sea transition, but the change from archaeocetes to modern cetaceans is poorly established. New fossil material of the recently recognized family Eomysticetidae from the upper Oligocene Otekaike Limestone includes a new genus and species, Waharoa ruwhenua, represented by skulls and partial skeletons of an adult, juvenile, and a smaller juvenile. Ontogenetic status is confirmed by osteohistology of ribs. Waharoa ruwhenua is characterized by an elongate and narrow rostrum which retains vestigial alveoli and alveolar grooves. Palatal foramina and sulci are present only on the posterior half of the palate. The nasals are elongate, and the bony nares are positioned far anteriorly. Enormous temporal fossae are present adjacent to an elongate and narrow intertemporal region with a sharp sagittal crest. The earbones are characterized by retaining inner and outer posterior pedicles, lacking fused posterior processes, and retaining a separate accessory ossicle. Phylogenetic analysis supports inclusion of Waharoa ruwhenua within a monophyletic Eomysticetidae as the earliest diverging clade of toothless mysticetes. This eomysticetid clade also included Eomysticetus whitmorei, Micromysticetus rothauseni, Tohoraata raekohao, Tokarahia kauaeroa, Tokarahia lophocephalus, and Yamatocetus canaliculatus. Detailed study of ontogenetic change demonstrates postnatal elaboration of the sagittal and nuchal crests, elongation of the intertemporal region, inflation of the zygomatic processes, and an extreme proportional increase in rostral length. Tympanic bullae are nearly full sized during early postnatal ontogeny indicating precocial development of auditory structures, but do increase slightly in size. Positive allometry of the rostrum suggests an ontogenetic change in feeding ecology, from neonatal suckling to a more specialized adult feeding behaviour. Possible absence of baleen anteriorly, a delicate temporomandibular joint with probable synovial capsule, non-laterally deflected coronoid process, and anteroposteriorly expanded palate suggests skim feeding as likely mode of adult feeding for zooplankton. Isotopic data in concert with preservation of young juveniles suggests the continental shelf of Zealandia was an important calving ground for latitudinally migrating Oligocene baleen whales.